A novel approach to tracing oncogenesis following von Hippel Lindau inactivation in mice - Kurlekar, S (2023)
Defining the early events following cancer mutation in cells of normal tissues is an enduring challenge in understanding the origins of cancer. In clear cell renal cell carcinoma (ccRCC) evolution, the inactivation of the ubiquitously-expressed von Hippel Lindau (VHL) tumour suppressor gene is a truncal event. However, VHL-associated oncogenesis is highly tissue-specific and can require years or decades between VHL inactivation and presentation of cancer. This raises unanswered questions as to the behaviour of VHL-null cells prior to neoplastic transformation and the contexts in which such transformation is supported.